IJTIMAK SEBAGAI PRASARAT PERGANTIAN BULAN BARU DALAM KALENDER HIJRIYAH (Studi Analisis Ijtimak Awal Bulan Syawwal 1441H): Membahas perbedaan dalam penentuan ijtimak - Nihayatur Rohmah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2020)
Analyzing the problem at the beginning of the Islamic month is basically based on the hadiths of rukyah and the Ulama 'differing opinions in understanding it so that it gives birth to differences of opinion. Some argue that the initial determination of Ramadan, Shawwal and Dhu al-Hijjah must be based on rukyah or seeing the new moon which is carried out on the 29th. Determination of the beginning of the Islamic month in the perspective of astronomy is to calculate the time of the occurrence of conjunctions or known as ijtima. Hilal visibility or rukyat hilal as a marker of the beginning of the month. Hilal can be formed if it has gone through its conjunction / ijtima phase. The number of days in a month consists of 29 days or 30 days. Determination of the beginning of the month by using the criteria for the visibility of the new moon and the presence of the new moon on the 29th of the Islamic month, it is often found under the horizon when the hilal rukyat activities on that date are carried out so that in the Hijriyah calendar there is a special concept if the new moon is not visible. Such conditions occurred at the beginning of the month of 1441 AH, where according to various calculation systems there were differences when ijtima occurred. According to the Sulam Nayyirain ijtimak calculation system occurred on the 29th of Ramadan, whereas according to another calculation system ijtima beginning in the month of syawwal only occurred on the 30th of Ramadlan 1441 H. Other data shows that the hilal position on the 29th of Ramadlan is still below the horizon so that the moon is impossible dirukyah. The difference between Muslims in determining the occurrence of ijtima in the end did not have an impact on the determination of the beginning of Shawwal, because of all the existing calculation systems, Muslims agreed to set the date of Shawwal 1441 H to occur on May 24, 2020 by applying the istikmal concept.